Dual Probes for Positron Emission Tomography (PET) and Fluorescence Imaging (FI) of Cancer - Richard Yuen; Frederick G. West; Frank Wuest (MDPI AG, 2022)
Dual probes that possess positron emission tomography (PET) and fluorescence imaging (FI) capabilities are precision medicine tools that can be used to improve patient care and outcomes. Detecting tumor lesions using PET, an extremely sensitive technique, coupled with fluorescence-guided surgical resection of said tumor lesions can maximize the removal of cancerous tissue. The development of novel molecular probes is important for targeting different biomarkers as every individual case of cancer has different characteristics. This short review will discuss some aspects of dual PET/FI probes and explore the recently reported examples.